Cell-Free Strategies for Repair and Regeneration of Meniscus Injuries through the Recruitment of Endogenous Stem/Progenitor Cells - Weimin Guo; Wenjing Xu; Zhenyong Wang; Mingxue Chen; Chunxiang Hao; Xifu Zheng; Jingxiang Huang; Xiang Sui; Zhiguo Yuan; Yu Zhang; Mingjie Wang; Xu Li; et al. (Stem Cells International)
The meniscus plays a vital role in protecting the articular cartilage of the knee joint. The inner two-thirds of the meniscus are avascular, and injuries to this region often fail to heal without intervention. The use of tissue engineering and regenerative medicine techniques may offer novel and effective approaches to repairing meniscal injuries. Meniscal tissue engineering and regenerative medicine typically use one of two techniques, cell-based or cell-free. While numerous cell-based strategies have been applied to repair and regenerate meniscal defects, these techniques possess certain limitations including cellular contamination and an increased risk of disease transmission. Cell-free strategies attempt to repair and regenerate the injured tissues by recruiting endogenous stem/progenitor cells. Cell-free strategies avoid several of the disadvantages of cell-based techniques and, therefore, may have a wider clinical application. This review first compares cell-based to cell-free techniques. Next, it summarizes potential sources for endogenous stem/progenitor cells. Finally, it discusses important recruitment factors for meniscal repair and regeneration. In conclusion, cell-free techniques, which focus on the recruitment of endogenous stem and progenitor cells, are growing in efficacy and may play a critical role in the future of meniscal repair and regeneration.